The Role of TLRs in Anti-cancer Immunity and Tumor Rejection - Urban-Wojciuk, Zuzanna; Khan, Mohd M.; Oyler, Benjamin L.; Fåhraeus, Robin; Marek-Trzonkowska, Natalia; Nita-Lazar, Aleksandra; Hupp, Ted R.; Goodlett, David R. (Frontiers in Immunology, 2019)
In recent years, a lot of scientific interest has focused on cancer immunotherapy. Although chronic inflammation has been described as one of the hallmarks of cancer, acute inflammation can actually trigger the immune system to fight diseases, including cancer. Toll-like receptor (TLR) ligands have long been used as adjuvants for traditional vaccines and it seems they may also play a role enhancing efficiency of tumor immunotherapy. The aim of this perspective is to discuss the effects of TLR stimulation in cancer, expression of various TLRs in different types of tumors, and finally the role of TLRs in anti-cancer immunity and tumor rejection.